Supercritical reaction between methanol and glycerol: The effects of reaction products on biodiesel properties - Winatta Sakdasri; Somkiat Ngamprasertsith; Pongrawee Saengsuk; Ruengwit Sawangkeaw (My University, 2021)
This work investigated the supercritical reaction between glycerol and supercritical methanol (SCM) in non-catalytic biodiesel production process. Glycerol is a by-product of biodiesel production that could react with SCM, producing glycerol ethers (GEs). Simultaneous conversion of triglycerides and glycerol in SCM is promising to reduce the glycerol surplus. These GEs are completely miscible with biodiesel and work as fuel enhancer. In a batch reactor, the glycerol reaction with SCM was investigated between 325 °C and 400 °C. The methanol-to-glycerol molar ratios and reaction time were varied from 3:1 to 9:1 and 8 min to 12 min, respectively. It was observed that the reactions of glycerol and SCM were etherification, dehydration, and thermal decomposition of glycerol. At molar ratios of 3:1 and 6:1, the temperature and reaction time significantly enhanced the glycerol conversion, especially by the thermal decomposition reaction. The increasing methanol-to-glycerol molar ratios reduced the overall glycerol conversion. The maximum glycerol conversion of 46.40% was observed at reaction temperature of 400 °C, methanol-to-glycerol molar ratio of 3:1, and reaction time of 12 min. Besides, the effects of GEs-to-neat biodiesel (B100) volumetric ratios on the fuel properties were investigated. The blending of GEs positively improved the viscosity and cloud point, whereas it had no impact on the heating value and flash point.
Keywords: Biodiesel Production and Applications